PERAN BRAND IMAGE, TRUST DAN AWARENESS TERHADAP BEHAVIORAL INTENTION MELALUI BRAND PREFERENCE, CUSTOMER PERCEIVED VALUE DAN SATISFACTION - ADIATI HARDJANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
The purpose of this paper is to analyze the role of brand image, brand trust, brand awareness toward behavioral intentions thru brand preference , customer perceived value, dan satisfaction. The paper aims to provide useful managerial implications for managers of Internet Service Provider. Research planning applied in this research is Testing Hypothesis. This research data obtained by distributing questionnaire to 120 respondents as consumers of Fastnet Internet Service Provider in Bekasi and Jakarta. Sample in this research applies purposive sampling technique. To analyze the relation between a number of key variables is applied instrument test consisted of validity test, and reliability test, and applied hypothesis test with Structural Equation Model. In this research, hypothesis brand image has impact to the brand preference not supported, but the other hypothesis are supported, so management should pay attentions to brand trust, brand awareness, brand preference and customer satisfaction to increase customer behavioral intention to purchase.